Digitalisasi Layanan Publik dan Dampaknya pada Ekologi Administrasi Sosial: Peluang dan Risiko - Sri Yulianty Mozin; Romy Tantu; Edis Adelia Dunggio; Siti Rukiah Yusup; Arit Pratama Putra Lihawa; Zavicka Aulia Natasya; Sabrina Meamogu; Siti Fadilah Atjil; Siti Nurain Tuna; Nopal R. Abas; Adeliptia Abdullah; Raihan Alamsyah Hilapah; Wal Fajri (Jurnal Media Administrasi, 2025)
This article explores the background, methods, results, and conclusions of digitalization in public services, focusing on its impact on the social administration ecology. It examines the rapid adoption of e- government and ICT (information and communication technology) by public administrations worldwide since 2020, investigating both opportunities and risks. Methods include a systematic literature review and qualitative case studies drawn primarily from peer-reviewed journals published between 2020 and 2024. The results show that digitalization in public services offers significant benefits: improved efficiency, transparency, citizen participation, reduced corruption, and enhanced environmental governance. However, it also presents risks, in particular widening digital divides, loss of human aspects in administrative interaction, ethical concerns (data privacy, algorithmic bias), regulatory and infrastructural challenges, and potential exclusion of marginalized groups. The discussion elaborates on how these opportunities and risks reshape the ecology of social administration defined here as the interplay of structures, actors, norms, technologies, and environment in public administration. In conclusion, the paper argues that digitalization must be managed with attention to equity, ethical governance, infrastructure readiness, and regulatory safeguards. Key recommendations include fostering digital literacy, inclusive design, transparency in data and algorithmic processes, and participatory governance.